Implementasi kurikulum berbasis Sociopreneur dalam pendidikan karakter di SMK Santa Maria Jakarta - Margareta Wahyu Dwi Utari (Inovasi Kurikulum, 2022)
Vocational High School is a form of formal education that provides vocational education. One of the points of competency standards for vocational high school graduates is personal and social character. Based on this, character education needs to be applied in vocational high schools, considering that vocational high schools are the ends of preparing the workforce in the face of global competition in the era of the Industrial Revolution 4.0. Santa Maria Vocational High School, one of the private vocational high schools in Central Jakarta, feels the need to have a distinctive character to compete in global challenges by applying sociopreneur values in every teaching and learning process called the sociopreneur curriculum. The purpose of this study was to determine the extent to which the sociopreneur curriculum's implementation impacted students' character, especially on the competence of fashion design skills at Santa Maria Vocational High School. The research method in the study used a qualitative approach with sampling through a purposive sampling technique and data collection by triangulation technique through observation, interviews, and documentation. The results of the study show that the sociopreneur values contained in the sociopreneur curriculum also have an impact on the character education of students, which is clearly visible in the relevance of sociopreneur values in everyday life and has experienced a significant increase in importance and the surrounding environment. AbstrakSekolah Menengah Kejuruan adalah salah satu bentuk pendidikan formal yang menyelenggarakan pendidikan kejuruan. Salah satu poin standar kompetensi lulusan SMK, yaitu karakter pribadi dan sosial. Berdasar hal tersebut, maka pendidikan karakter perlu diterapkan di SMK mengingat SMK menjadi ujung tombak penyiapan tenaga kerja dalam menghadapi persaingan global di era revolusi industri 4.0. SMK Santa Maria sebagai salah satu sekolah menengah kejuruan swasta yang berlokasi di Jakarta Pusat merasa perlu memiliki ciri khas agar dapat bersaing dalam tantangan global dengan menerapkan nilai-nilai sociopreneur pada setiap proses belajar mengajar yang disebut dengan kurikulum sociopreneur, Tujuan dari penelitian ini adalah mengetahui sejauh mana implementasi kurikulum sociopreneur berdampak pada karakter peserta didik khususnya pada kompetensi keahlian Tata Busana di SMK Santa Maria. Metode penelitian menggunakan kualitatif dengan pengambilan sampel melalui teknik purposive sampling dan pengumpulan data dengan teknik triangulasi melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa nilai-nilai sociopreneur yang terkandung pada kurikulum sociopreneur turut memberi dampak pada pendidikan karakter peserta didik yang terlihat secara nyata pada relevansi nilai-nilai sociopreneur dalam kehidupan sehari-hari yang dialami dan merasakan peningkatan yang signifikan terhadap kepedulian dan kepekaan terhadap lingkungan sekitar.Kata Kunci: Implementasi kurikulum; pendidikan karakter; sociopreneur